Hell's bride : research and remediation of Chinese ghost weddings - Ng, Pei Wen (Nanyang Technological University, 2021)
Hell's Bride is an experimental stop-motion animation that explores the history behind a little known Chinese custom called 冥婚 (ming hun) or Ghost Wedding. Through the synthesis of various traditional and digital processes, and by focusing on Chinese and ghost weddings, the project is a visualisation of the artist's abstract understanding of Chinese traditions, customs and dialects. This is a comprehensive documentation of the research behind the history of Chinese ghost weddings, Chinese symbolism and the creative and technical processes of the film. With the marriage of paper props, sinister puppets and a bizarre bride, the stage for an uncanny wedding is set.